Iro/IRX transcription factors negatively regulate Dpp/TGF-? pathway activity during intestinal tumorigenesis. - Martorell, O.; Barriga, F.M.; Merlos-Suárez, A.; Stephan-Otto Attolini, C.; Casanova, J.; Batlle, E.; Sancho, E.; Casali, A. (EMBO Reports, 2014)
Activating mutations in Wnt and EGFR/Ras signaling pathways are common in colorectal cancer (CRC). Remarkably, clonal co-activation of these pathways in the adult Drosophila midgut induces "tumor-like" overgrowths. Here, we show that, in these clones and in CRC cell lines, Dpp/TGF-? acts as a tumor suppressor. Moreover, we discover that the Iroquois/IRX-family-protein Mirror downregulates the transcription of core components of the Dpp pathway, reducing its tumor suppressor activity. We also show that this genetic interaction is conserved in human CRC cells, where the Iro/IRX proteins IRX3 and IRX5 diminish the response to TGF-?. IRX3 and IRX5 are upregulated in human adenomas, and their levels correlate inversely with the gene expression signature of response to TGF-?. In addition, Irx5 expression confers a growth advantage in the presence of TGF-?, but is selected against in its absence. Together, our results identify a set of Iro/IRX proteins as conserved negative regulators of Dpp/TGF-? activity. We propose that during the characteristic adenoma-to-carcinoma transition of human CRC, the activity of IRX proteins could reduce the sensitivity to the cytostatic effect of TGF-?, conferring a growth advantage to tumor cells prior to the acquisition of mutations in TGF-? pathway components.